Use of historical information in extreme-surge frequency estimation: the case of marine flooding on the La Rochelle site in France - Y. Hamdi; L. Bardet; C.-M. Duluc; V. Rebour (Natural Hazards and Earth System Sciences, 2015)
Nuclear power plants located in the French Atlantic coast are designed to be protected against extreme environmental conditions. The French authorities remain cautious by adopting a strict policy of nuclear-plants flood prevention. Although coastal nuclear facilities in France are designed to very low probabilities of failure (e.g., 1000-year surge), exceptional surges (outliers induced by exceptional climatic events) have shown that the extreme sea levels estimated with the current statistical approaches could be underestimated. The estimation of extreme surges then requires the use of a statistical analysis approach having a more solid theoretical motivation. This paper deals with extreme-surge frequency estimation using historical information (HI) about events occurred before the systematic record period. It also contributes to addressing the problem of the presence of outliers in data sets. The frequency models presented in the present paper have been quite successful in the field of hydrometeorology and river flooding but they have not been applied to sea level data sets to prevent marine flooding. In this work, we suggest two methods of incorporating the HI: the peaks-over-threshold method with HI (POTH) and the block maxima method with HI (BMH). Two kinds of historical data can be used in the POTH method: classical historical maxima (HMax) data, and over-a-threshold supplementary (OTS) data. In both cases, the data are structured in historical periods and can be used only as complement to the main systematic data. On the other hand, in the BMH method, the basic hypothesis in statistical modeling of HI is that at least one threshold of perception exists for the whole period (historical and systematic) and that during a giving historical period preceding the period of tide gauging, only information about surges above this threshold have been recorded or archived. The two frequency models were applied to a case study from France, at the La Rochelle site where the storm Xynthia induced an outlier, to illustrate their potentials, to compare their performances and especially to analyze the impact of the use of HI on the extreme-surge frequency estimation.